Rancang Bangun Robot Pembuat Sketsa Gambar Menggunakan Raspberry Pi - Asril Basry (Fakultas Teknik Universitas Persada Indonesia YAI, 2020)
Art is not that complicated, because there are no limitations in terms of technique, perception, and media creation. However, from various points of view, the assessment of artwork either good or not are depend on the meaning and quality of the artwork. Therefore, the process of making an artwork can be done by sketching an image first. The process of making sketch can be done manually using a pencil but which takes a lot of time. Along with the technological development today, its usage can simplify the process of creating artworks. From the summary of problems above, then a tool for sketching artwork was designed using hardware such as Rasberry Pi, Driver Motor L298N, Motor Stepper, and Motor Servo. All these components are assembled and programmed in order to help the process of making a sketch image based on the selected object.